MEDIA PEMBELAJARAN MENULIS SUBMATERI EYD DENGAN MACROMEDIA AUTHORWARE 7.0 UNTUK SISWA KELAS XI SMA/MA - Septiana Farida (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This research is conducted to develop a computer assisted learning media to teachwriting sub‐material EYD (Ejaan Yang Disempurnakan) by using Macromedia Authorware 7.0and to find out the quality of the media in the form of CD so that it is applicable as analternative learning. The research was carried out by referring to Borg and Gail, but in its progress it was simplified into six steps which are (1) Doing need analysis, (2) Developing the product, (3)Validating the program by the user and expert judgment, (4) Revising the product, (5)Testing the product using two pre‐tests and post‐tests, (6) Revising the final product. Thesubjects were the second semester students of XI IPS 3 MAN Yogyakarta III. The data wereobtained from the questionnaires with a 1‐4 scale rating converted according to theassessment criteria. The data also came with a limited trial result through the pre‐test andpost‐test by students. The results ofthe product validation by two experts ofmaterial and media showed thescores with the criteria ofprofoundly agree. Phase I of the user validation produced a meanscore in the criteria of profoundly agree. The second phase of validation produced a meanscore in the criteria of profoundly agree in terms of the appearance and learning aspects,and the mean score with the agree criteria in terms of the content / learning aspects. Theresults ofthe pre‐test and post‐test in the both phases showed an increasing average scoreby 10% for the first phase and 10.875% for the second phase.Keywords : learning media, writing, EYD